Protective effect of Ganoderma lucidum-fermented crop extracts against hydrogen peroxide- or β-amyloid-induced damage in human neuronal SH-SY5Y cells - Chung-Hsiung Huang; Yu-Ting Liao; Chien-Li Chen; Guo-Jane Tsai (BMC, 2024)
Abstract Background Alzheimer's disease (AD) is a neurodegenerative disorder characterized by the accumulation of stacked β-amyloid peptides in the brain and associated with the generation of oxidative stress. So far, there is no cure for AD or a way to stop its progression. Although the neuroprotective effects of Ganoderma lucidum aqueous extract and G. lucidum-derived triterpenoids and polysaccharides have been reported, the influence of G. lucidum-fermented crops on AD still lacks clarity. Methods This study aimed to investigate the protective effect of G. lucidum-fermented crop extracts against hydrogen peroxide- or β-amyloid peptide (Aβ25-35)-induced damage in human neuroblastoma SH-SY5Y cells. Results Various extracts of G. lucidum-fermented crops, including extract A: 10% ethanol extraction using microwave, extract B: 70˚C water extraction, and extract C: 100˚C water extraction followed by ethanol precipitation, were prepared and analyzed. Extract B had the highest triterpenoid content. Extract C had the highest total glucan content, while extract A had the highest gamma-aminobutyric acid (GABA) content. The median inhibitory concentration (IC50, mg/g) for DPPH and ABTS scavenging activity of the fermented crop extracts was significantly lower than that of the unfermented extract. Pretreatment with these extracts significantly increased the cell viability of SH-SY5Y cells damaged by H2O2 or Aβ25-35, possibly by reducing cellular reactive oxygen species (ROS) and malondialdehyde (MDA) levels and increasing superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT) activities. Moreover, extract B markedly alleviated the activity of acetylcholinesterase (AChE), which is crucial in the pathogenesis of AD. Conclusion These results clearly confirmed the effects of G. lucidum-fermented crop extracts on preventing against H2O2- or Aβ25-35-induced neuronal cell death and inhibiting AChE activity, revealing their potential in management of AD.